On the Extent of Economic Integration: A Comparison of EU Countries and US States - Harry P. Bowen; Haris Munandar; Jean-Marie Viaene (Tinbergen Institute, 2010)
European economic integration is commonly believed to be incomplete, and that further reforms are needed. In this context, the union of U.S. states is considered the benchmark of complete economic integration and is often the basis for comparison regarding the extent of E.U economic integration. Yet, with low trade barriers and with productive factors at least notionally mobile across E.U. countries, is the belief that U.S. states are more integrated than E.U. member states correct? To address this question, this paper first develops three theoretical predictions about the distribution of output and factors that would arise among members of a fully integrated economic area in which goods, capital and labor are freely mobile and policies are harmonized. These theoretical predictions are then empirically tested using data on the output and factor stocks of 14 E.U. member states and the 51 U.S. states (includes District of Columbia) for the period 1965 to 2000. The empirical results convincingly support each theoretical prediction. Hence, contrary to popular belief, the extent of E.U. economic integration is not statistically different from that among U.S. states.
Keywords: E13; F15; F21; F22; F4; O57; 330; Economic integration; capital mobility; factor price equalization; Brownian motion; Zipf's law; Marktintegration; Kapitalmobilität; Stochastischer Prozess; Statistische Verteilung; EU-Staaten; Vergleich; Teilstaat; USA